The Educational Strategies of Islamic Boarding Schools in Instilling Entrepreneurial Spirit in Students at Pondok Pesantren Darul Amien, Jajag Gambiran Banyuwangi - Mufasirul Bayani (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
Pondok Pesantren (Islamic boarding schools) are one of the educational institutions that are able to produce intellectual generations with independent characters. This study aims to analyze: (1) the strategy of Islamic boarding schools in instilling an entrepreneurial spirit in students at the Darul Amien Jajag Gambiran Banyuwangi Islamic Boarding School, (2) the implementation of educational activities that instill an entrepreneurial spirit in students, and (3) the impact of entrepreneurial education on students at the Darul Amien Jajag Gambiran Banyuwangi Islamic Boarding School. This study uses a qualitative method, with researchers going directly to the location to obtain valid data through observation, interviews, and documentation. The data obtained were analyzed using data reduction techniques, data presentation, and drawing conclusions. The results of the study indicate that: (1) the strategy for instilling an entrepreneurial spirit in the Darul Amien Islamic Boarding School includes a planning strategy, a tactical strategy, and a behavioral pattern strategy; (2) the implementation of educational activities to instill an entrepreneurial spirit in students involves instilling a vision, commitment, self-confidence, discipline, readiness to take risks, concern for consumers, and creativity; (3) The impact of this entrepreneurship education is that students become more self-confident, have thoughts that are directed towards the future, dare to face challenges, and have creativity and innovation in creating new things. This forms a strong leadership spirit, which is important for becoming a successful entrepreneur.